Membrane Vesicles Are the Dominant Structural Components of Ceftazidime-Induced Biofilm Formation in an Oxacillin-Sensitive MRSA - He, Xinlong; Li, Shuang; Yin, Yi; Xu, Jiahui; Gong, Weijuan; Li, Guocai; Qian, Li; Yin, Yinyan; He, Xiaoqin; Guo, Tingting; Huang, Yuzheng; Lu, Feng; et al. (Frontiers in Microbiology, 2019)
Methicillin-resistant S. aureus (MRSA) has received increasing attention in recent years. However, the characteristics and relevant mechanisms of biofilm formation in oxacillin-sensitive MRSA (OS-MRSA) are poorly understood. This study was designed to characterize biofilm formation in OS-MRSA BWSA15 in response to ceftazidime (TZ) by comparing the methicillin-sensitive S. aureus (MSSA) strain BWSA23 and the oxacillin-resistant MRSA (OR-MRSA) strain BWSA11.The biofilms and biofilm-forming cells were observed by electron microscopy. Biofilms grown on microtiter plates were chemically decomposed and analyzed by Fourier transform infrared spectroscopy. The transcriptional regulation of genes associated with methicillin resistance, surface adhesion, fatty acid biosynthesis, and global regulation (sigma B) was investigated. A significant increase in biofilm formation ability (10.21-fold) and aggregation ability (2.56-fold) was observed in BWSA15 upon the treatment with TZ (16μg/ml). The TZ-induced biofilm formation in BWSA15 was characterized by a disappearance of polysaccharide-like extracellular substances and an appearance of a large number of intercellular MVs from extracellular matrix. Few MVs were identified in the biofilms formed by BWSA11 and BWSA23. There was a significant upregulation of mecA, sigB and fatty acid biosynthesis-associated genes and downregulation of icaA, icaD, clfA, clfB and fnaA in BWSA15 upon the treatment with TZ. The formation of intracellular junctions of MVs in the biofilms of BWSA15was mediated by a significant increase in the proportion of proteins as well as by an increase in the proportion of nonionized carboxyl groups in fatty acids. This study demonstrated that beta-lactam antibiotics can induce biofilm formation in OS-MRSA, and the biofilm induction in OS-MRSA can mainly be attributed to exposed MVs with increased hydrophobicity rather than polysaccharide intercellular adhesins, cell wall-anchored surface proteins and extracellular DNA.